Integration of Artificial Intelligence in Islamic Religious Education Learning in Vocational Schools - Wiwin Fachrudin Yusuf; Nike Febrian Imelda; Abdul Kholiq (Program Studi Pendidikan Agama Islam, Fakultas Tarbiyah, Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2026)
The development of Artificial Intelligence has brought changes to student learning practices, including in Islamic Religious Education (PAI) in Vocational High Schools. This AI integration not only expands access to religious knowledge but also raises challenges related to academic integrity. This study aims to describe students’ use of AI in Islamic Education (PAI) classes, analyze students’ perceptions of technology use within the framework of academic integrity, and identify teachers’ pedagogical strategies for mediating AI use so that it remains consistent with the values internalized in the learning process. This study uses a qualitative case study design. Data was collected through in-depth interviews, learning observations, and assignment documentation, and was analyzed thematically. The results show that AI is integrated into learning practices as a tool for understanding the material and composing responses. Students show an ambivalent ethical dynamic between technological efficiency and academic honesty norms. Teachers' pedagogical practices function as a mediation through authentic assessments, reflective dialogues, and the affirmation of the value of honesty, integrated into the learning process. Students also negotiate the use of AI by modifying the results and combining them with other sources. These findings suggest that AI integration does not directly erode academic integrity but shifts its practice toward a more contextual and situational approach, depending on pedagogical design and the intensity of teacher mediation. The study also shows that religious values serve as a normative framework that shapes how learners interpret and use AI in the context of academic honesty.